A combined proteomic and immunologic approach for the analysis of Schistosoma mansoni cercariae and adult worm protein extracts and the detection of oneof the vaccine candidates, Sm28GST,from a Venezuelan parasite isolate - Losada, Sandra; Sabatier, Laurence; Hammann, Philippe; Guillier, Christelle; Matos, César; Bermúdez, Henry; Lorenzo, María Angelita; Noya, Oscar (Investigación Clínica, 2013)
Understanding the mode of Schistosoma mansoni larval invasion and the mechanism of immune evasion utilized by larvae and adult worms is essential for a rational development of vaccines or drugs to prevent or cure the disease. This parasite has a very complex molecular organization in all parasite stages, and identifying the major parasite proteins would give clues to schistosome metabolism and to the interaction of the parasite with the host immune system. Our goal was the evaluation of the protein parasite repertoire using a proteomic approach, and the characterization of protein extracts from two different parasite stages of a Venezuelan isolate, such as cercariae and adult worms, previously performed by other authors in some other strains. A comparison among authors was made. Besides, we aimed toidentify different isoforms of one of the vaccine candidates, the gluthation- S-transferase protein (Sm28GST), by 2D SDS-PAGE and mass spectrometry, and to achieve its immunologic detection using sera from rabbits immunized with synthetic peptides derived from the Sm28GST protein. These techniques allowed the identification of some of the target molecules of the protective immune response that are being evaluated as potential members of amulti-component and multi-stage anti-S. Mansoni vaccine and to clarify if the selected peptides induce antibodies that are able to recognize different isoforms of the Sm28GST.